2018
DOI: 10.3389/fncel.2018.00436
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Intrinsic Excitability of Pyramidal Neurons in Anterior Cingulate Cortex in Neuropathic Pain

Abstract: To find satisfactory treatment strategies for neuropathic pain syndromes, the cellular mechanisms should be illuminated. Central sensitization is a generator of pain hypersensitivity, and is mainly reflected in neuronal hyperexcitability in pain pathway. Neuronal excitability depends on two components, the synaptic inputs and the intrinsic excitability. Previous studies have focused on the synaptic plasticity in different forms of pain. But little is known about the changes of neuronal intrinsic excitability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…For sham-operated mice, the sciatic nerve was exposed without axon incision and ligation, and muscle and skin layers were then carefully sutured. The complete sural nerve should not be stretched during the operation [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…For sham-operated mice, the sciatic nerve was exposed without axon incision and ligation, and muscle and skin layers were then carefully sutured. The complete sural nerve should not be stretched during the operation [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pyramidal neurons in L2/3 are nociceptive and show regular spiking, intermediate firing, or intrinsic bursting [68,69]. Excitatory pyramidal neurons in layers L2/3 and L5 respond to noxious mechanical and thermal stimuli with an increase in firing rates and are related to the unpleasantness induced by acute pain [69][70][71][72][73][74]. Pain conditions including peripheral nerve injury induce long-lasting synaptic plasticity by different variations of long-term potentiation (LTP) or long-term depression (LTD) to increase excitatory synaptic transmission resulting in hyperexcitability and disinhibition of the ACC, whereas inhibitory transmission is reduced [68,[75][76][77][78][79][80].…”
Section: Pyramidal Neuronsmentioning
confidence: 99%
“…The ACC is the most dorsal subregion of the mPFC and often studied separately due to its prominent role in the affective component of pain processing [146]. Neuropathy enhances presynaptic glutamate release, postsynaptic AMPA mediated response as well as excitability of ACC layer L2/3 pyramidal neurons, in particular those which are intermediately firing [68,73,75,144]. Apart from augmented glutamatergic transmission, prolonged nociceptive sensitization during the initial induction phase can weaken inhibitory control in layer L2/3 as indicated by reduced frequency of miniature and spontaneous inhibitory postsynaptic currents, suggesting presynaptic GABAergic plasticity [147].…”
Section: Layer 2/3mentioning
confidence: 99%
“…The potentiation of synaptic transmission in the ACC was reported to be the key mechanism underlying neuropathic pain. 8 , 9 , 48 And a study showed that the activation of Notch signaling regulates synaptic transmission in the hippocampus. 1 Thus, given the possible link between synaptic transmission and the Notch signaling pathway in the pathological process of neuropathic pain, we further confirmed that the shRNA-Notch1-expressing recombinant AAV decreased excitatory synaptic transmission using electrophysiological techniques.…”
Section: Discussionmentioning
confidence: 99%